Pests, Weeds and Diseases in Agricultural Crop and Animal Husbandry Production - Kontogiannatos, Dimitrios; Kourti, Anna; Ferreira Mendes, Kassio (IntechOpen, 2020)
This book highlights some of the most recent research with respect to emerging pest challenges in agricultural crop and animal husbandry production: analytical methods for glyphosate detection in foods, biopesticides and essential oils, environmental safety in pest control, herbicide and glyphosate resistance, herbicides and weed management, integrated pest management, mass spectrometry for insect physiology studies, pheromones and chemical communication, pasteurellosis outbreaks, and tick identification and management.